2023
DOI: 10.1002/ange.202217622
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolostasis Network and the Cellular Depository of Aggregation‐Prone Metabolites

Abstract: The vital role of metabolites across all branches of life and their involvement in various disorders have been investigated for decades. Many metabolites are poorly soluble in water or in physiological buffers and tend to form supramolecular aggregates. On the other hand, in the cell, they should be preserved in a pool and be readily available for the execution of biochemical functions. We thus propose that a quality‐control network, termed “metabolostasis”, has evolved to regulate the storage and retrieval of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…The fibril-to-crystal interconversion (and vice versa) has been a fascinating but difficult event to capture. Crystal structures of amyloid fibrils have been used for decades to elucidate structures of biologically relevant amyloid fibrils. , In parallel, the fibril-to-crystal transitions are fundamental to materials science in a broader context for applications across medicine to nanotechnology. …”
Section: Introductionmentioning
confidence: 99%
“…The fibril-to-crystal interconversion (and vice versa) has been a fascinating but difficult event to capture. Crystal structures of amyloid fibrils have been used for decades to elucidate structures of biologically relevant amyloid fibrils. , In parallel, the fibril-to-crystal transitions are fundamental to materials science in a broader context for applications across medicine to nanotechnology. …”
Section: Introductionmentioning
confidence: 99%
“…Phe fibrils, such as conventional amyloid, could bind to Congo red (CR) and ThT dyes and were cytotoxic to neural cell lines. The study suggested a common etiology between phenylketonuria (PKU), an IEM caused by the accumulation of Phe, and amyloid-associated disorders such as Alzheimer’s and Parkinson’s diseases . This path-breaking research, for the very first time, showed that the study of aggregation of metabolites is of crucial significance as it may be the underlying cause leading to the pathogenesis in IEMs, and hence, a ‘generic amyloid hypothesis’ was proposed.…”
Section: Introductionmentioning
confidence: 99%